2022
DOI: 10.1080/19490976.2022.2105102
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori actively suppresses innate immune nucleic acid receptors

Abstract: Chronic mucosal pathogens have evolved multiple strategies to manipulate the host immune response; consequently, microbes contribute to the development of >2 million cases of cancer/year. Gastric adenocarcinoma is the fourth leading cause of cancer-related death and Helicobacter pylori confers the highest risk for this disease. Gastric innate immune effectors can either eliminate bacteria or mobilize adaptive immune responses including Toll-like receptors (TLRs), and cytosolic DNA sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 73 publications
0
12
1
Order By: Relevance
“…A key finding of our study was that AIM2 messenger RNA and protein levels were upregulated in H. pylori –positive human gastric biopsies and gastric tissues from H. felis– infected mice, consistent with inflammasome activity. Interestingly, this contrasts recent findings that other DNA sensors, namely, stimulator of interferon genes (STING) and retinoid acid inducible gene I (RIG‐I), are downregulated by Helicobacter in an 8‐week infection mouse model where deletion of Sting1 or Rigi reduced acute immune responses but not chronic gastric inflammation 32 . The expression of both these genes also negatively correlates with GC prognosis in patients 32–34 .…”
Section: Discussioncontrasting
confidence: 57%
“…A key finding of our study was that AIM2 messenger RNA and protein levels were upregulated in H. pylori –positive human gastric biopsies and gastric tissues from H. felis– infected mice, consistent with inflammasome activity. Interestingly, this contrasts recent findings that other DNA sensors, namely, stimulator of interferon genes (STING) and retinoid acid inducible gene I (RIG‐I), are downregulated by Helicobacter in an 8‐week infection mouse model where deletion of Sting1 or Rigi reduced acute immune responses but not chronic gastric inflammation 32 . The expression of both these genes also negatively correlates with GC prognosis in patients 32–34 .…”
Section: Discussioncontrasting
confidence: 57%
“…Evasion of RIG-I-mediated innate immune responses may help EBV-infected cells transformation. Except for viruses, H. pylori also actively suppresses STING and RIG-I signaling via the downregulation of IRF3 activation [ 106 ]. Decreased RIG-I expression is associated with poor prognosis and promotes cell invasion in human gastric cancer and HCC [ 107 , 108 ].…”
Section: Rationale For Therapeutic Targeting Rlrs In Cancermentioning
confidence: 99%
“…The stimulation of the RIG-I receptor leads to the activation of the transcription factors IRF3 and IRF7 and subsequent expression of IFN-I (233). According to in vitro and ex vivo experiments, recently it was shown that through the downregulation of IRF3 activation, H. pylori actively inhibits cyclic GMP-AMP (cGAMP) synthase (cGAS)-stimulator of interferon genes (STING) and RIG-I signalling (234). DCs-specific intercellular adhesion molecule-3 grabbing non-integrin (DC-SIGN) is a member of the CLR family which plays a critical role in H. pylori recognition and pathogenesis.…”
Section: Escape From Innate Immune Recognitionmentioning
confidence: 99%